Effects of Combining Meditation Techniques on Short-Term Memory, Attention, and Affect in Healthy College Students - Pragya, Samani Unnata; Mehta, Neelam D.; Abomoelak, Bassam; Uddin, Parvin; Veeramachaneni, Pushya; Mehta, Naina; Moore, Stephanie; Jean-Francois, Melissa; Garcia, Stephanie; Pragya, Samani Chaitanya; Mehta, Devendra I. (Frontiers in Psychology, 2021)
Meditation refers to a family of self-regulation practices that focuses on training attention and awareness to foster psycho-emotional well-being and to develop specific capacities such as calmness, clarity, and concentration. We report a prospective convenience-controlled study in which we analyzed the effect of two components of Preksha Dhyāna – buzzing bee sound meditation (Mahapran dhvani) and color meditation (leśyā dhyāna) on healthy college students. Mahapran and leśya dhyāna are two Preksha Dhyāna practices that are based on sound and green color, respectively. The study population represents a suitable target as college students experience different stress factors during the school year. This study measures the individual and combined effects of two techniques (one focusing on sound and one focusing on color), on short-term memory, attention, and affect, in novice meditators. We used a battery of cognitive, performance, and compared results with baseline and control values. We found improved cognition, especially attention, short-term memory, and affect in terms of positivity and reduced negativity. Overall, the two techniques produced variable benefits and subjects showed improved scores over baseline for short-term memory, cognitive function, and overall wellbeing. Further studies are required to understand underlying mechanisms for the observed differences between the two techniques and to elucidate mechanisms underlying the more pronounced and global benefits observed with the combined techniques. These results underscore a need to examine individual components of meditation practices in order to individualize treatment approaches for attention disorders in young adults. Clinical Trail Registration:ClinicalTrials.gov Identifier: NCT03779269.